1960
DOI: 10.1051/animres:19600201
|View full text |Cite
|
Sign up to set email alerts
|

Mesure De La Production Laitière Des Brebis Pendant La Période d'ALLAITEMENT

Abstract: animale, ('. N. R. Z., Jouy-en-Joas (S. et 0.) SOMMAIRE La mesure de la production laitière des brebis au cours de l'allaitement nécessite la mise au point d'une méthode de contrôle particulière. Une des techniques le plus souvent utilisée est la mesure indirecte de la production des mères par pesée des agneaux avant et après la tétée.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

1967
1967
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Daily milk production was determined using oxytocin (3 IU) as in the method described by Ricordeau et al [34]. At each occasion of milk production recording (hand milking), samples of 20 mL of milk were also taken and immediately sent to the laboratory for analysis of fat and protein contents using an integrated milk testing machine (Combifoss 5300, Foss Electric, Denmark).…”
Section: Milk Productionmentioning
confidence: 99%
“…Daily milk production was determined using oxytocin (3 IU) as in the method described by Ricordeau et al [34]. At each occasion of milk production recording (hand milking), samples of 20 mL of milk were also taken and immediately sent to the laboratory for analysis of fat and protein contents using an integrated milk testing machine (Combifoss 5300, Foss Electric, Denmark).…”
Section: Milk Productionmentioning
confidence: 99%
“…Two hours later, the procedure was repeated and the milk volume was measured (Reynolds and Brown, 1991). This amount of milk represented 2-h milk production, which corresponds to normal suckling intervals of lambs at this age (Ricordeau et al, 1960). Within collection period, milk volume (milliliters) was adjusted to a 2-h production period for each ewe.…”
Section: Milk Productionmentioning
confidence: 99%
“…Bubenik found the sucking periods averaged 100 sec in duration, with an average milk intake per period in the first 4 weeks of 370 ml. Lambs suck rather more frequently (Ricordeau, Boccard & Denamur, 1960;Ewbank, 1967). Wallace (1948) found that lambs could drink a 4-hr milk production at one sucking, and Munro & Inkson (1957) found no difference in the yield of ewes when measured by 1-and 4-hr suckings.…”
Section: Milk Yieldsmentioning
confidence: 99%